Legal Protection of Music Copyrights in Public Commercial Spaces: A Case Study of Coffee Shops in Kolaka Utara Regency, Indonesia - Sari Angraeni, Besse; Somefotorono Majid, Pipit (IAIN Bone, 2025)
Legal protection of music copyrights is essential to ensure the economic and moral rights of creators. This study examines the legal protection of music copyrights in public commercial spaces, with a specific focus on coffee shops in North Kolaka, Indonesia. Using a normative juridical research method and a statutory approach, the analysis is based on relevant legal instruments, including Law Number 28 of 2014 on Copyright and Government Regulation Number 56 of 2021 on the Management of Royalties for Song and/or Music Copyrights. The findings reveal that several coffee shops play music in their business premises without obtaining permission from the creators or paying the required royalties. Such practices constitute copyright infringement and violate the exclusive rights protected under Indonesian copyright law, potentially resulting in criminal sanctions—including substantial fines and imprisonment—as well as civil liabilities in the form of damages and injunctions. The study concludes that coffee shop operators are legally obligated to pay royalties through the National Collective Management Organization (LMKN). It further highlights the significant role of Collective Management Organizations (LMK) and LMKN in ensuring copyright protection, particularly in royalty collection, distribution, enforcement, and dispute resolution.